VCD spectroscopy as an excellent probe of chiral metal complexes containing a carbon monoxide vibrational chromophore1. Issue 45 (7th June 2015) - Fusè, Marco; Mazzeo, Giuseppe; Longhi, Giovanna; Abbate, Sergio; Zerla, Daniele; Rimoldi, Isabella; Contini, Alessandro; Cesarotti, Edoardo
<x xml:space="preserve">Abstract</x> η5-Menthyl-C5H4Ru(ii) carbonyl complexes show VCD of CO; the stretching is very sensitive and diagnostic to the (R)Ru/(S)Ru metal chirality.